Transitional shale quality and exploration potential: A case study from the Lower Carboniferous Jiusi Formation in northwest Weining, China - Zeng, Jianli; Zhang, Tingshan; Yang, Wei; Zhu, Haihua; Zhang, Zhao; Li, Hongjiao; Bai, Yuhang; Gao, Lubiao (Frontiers in Earth Science, 2022)
The organic-rich shale of the early Carboniferous Jiusi Formation in Weining area, Southwestern China, has large geological gas reserves, making of the Jiusi Formation another target after the Ordovician-Silurian marine shale in South China. The complex superposition of multi-stage, tectonic phases since the Himalayan paroxysmal phase induced a series of controversies in the sedimentology of the Jiui Formation, as only few drillings were executed. In order to better understand the development potential of the shale associated with the Jiui Formation, five outcrops and a well (YS302) were studied, clarifying the sedimentary evolution of the formation, while two 2D seismic sections were used to analyze the regional structural styles. The result shows that the Jiusi Formation was significantly influenced by the synsedimentary extension of the northwestern margin of the Yadu-Ziyun-Luodian Fault, with the depositional center of Jiusi Formation extending to well YS302 along a NW direction, and asymmetrically thinning in A NE - SW direction. 15 lithofacies and three facies associations were identified, from tidal or delta settings to lagoon environments, finally turning into platform facies the base of the Shangsi Formation. According to the geochemical analysis of 27 core samples and 37 outcrop samples, as well as the well YS302 logging interpretation result. The transitional Jiusi shale in Weining area has a strong heterogeneity, high TOC values being mostly provided by the surrounding coal seams. XRD analyses show that the minerals of the transitional shale are dominated by a high clay content (42 wt%). The content of water-sensitive minerals in Jiusi shale is also relatively high, with clay minerals dominated by an illite/smectite mixture (52.8 %). When compared with the commercially developed Ordovician-Silurian marine shale, the Jiusi transitional shale shows a relatively poor quality, related to dense bioturbation and terrestrial input affecting the preservation of organic matter. Therefore, the evaluation standard of marine shale is difficult to apply to the transitional Jiusi shale. The cumulative thickness shale in YS302 worthy of shale gas development is nearly 100m. Meanwhile, considering that the transitional shales are often interlayered with coals, the shale gas and coalbed methane can be developed together.